Learning from the past: from incubation in ancient Egypt and Greece to modern hypnosis - Facco, Enrico; Tagliagambe, Silvano (Advances in Social Sciences Research Journal, 2021)
The origin of hypnosis can be dated back to ancient philosophies and medicines. Incubation had been used in ancient Egypt and Greece for some three millennia with the same indications of modern hypnosis and was well-known by both Hippocrates and Parmenides. Then, it was dismantled by Christian hagiographic propaganda in 4-5th century AC and buried to the oblivion. Again, the birth of the new sciences in 17th century was the result of a compromise with Church, forcing them to limit their field of interest in the Cartesian res extensa only, leading to consciousness and mind-body relationship being neglected for political-religious will, rather than scientific grounds, and to Hippocrates’ teaching being betrayed. As a result, the history of hypnosis was marked by its outstanding results paralleled by misunderstanding and prejudicial refusal, a fact endowed with deep epistemological implications.